Molecular docking based virtual screening of natural compounds as potential BACE1 inhibitors: 3D QSAR pharmacophore mapping and molecular dynamics analysis - Kumar, Akhil; Roy, Sudeep; Tripathi, Shubhandra; Sharma, Ashok (Journal of biomolecular structure & dynamics, 2016)
Beta-site APP cleaving enzyme1 (BACE1) catalyzes the rate determining step in the generation of Aβ peptide and is widely considered as a potential therapeutic drug target for Alzheimer's disease (AD). Active site of BACE1 contains catalytic aspartic (Asp) dyad and flap. Asp dyad cleaves the substrate amyloid precursor protein with the help of flap. Currently, there are no marketed drugs available against BACE1 and existing inhibitors are mostly pseudopeptide or synthetic derivatives. There is a need to search for a potent inhibitor with natural scaffold interacting with flap and Asp dyad. This study screens the natural database InterBioScreen, followed by three-dimensional (3D) QSAR pharmacophore modeling, mapping, in silico ADME/T predictions to find the potential BACE1 inhibitors. Further, molecular dynamics of selected inhibitors were performed to observe the dynamic structure of protein after ligand binding. All conformations and the residues of binding region were stable but the flap adopted a closed conformation after binding with the ligand. Bond oligosaccharide interacted with the flap as well as catalytic dyad via hydrogen bond throughout the simulation. This led to stabilize the flap in closed conformation and restricted the entry of substrate. Carbohydrates have been earlier used in the treatment of AD because of their low toxicity, high efficiency, good biocompatibility, and easy permeability through the blood-brain barrier. Our finding will be helpful in identify the potential leads to design novel BACE1 inhibitors for AD therapy.
Keywords: sekretasy; Heparitin Sulfate; Inhibitory Concentration 50; Ligands; Oligosaccharides; vodíková vazba; flap; β-secretase; Drug Evaluation, Preclinical; Humans; preklinické hodnocení léčiv; ligandy; Algorithms; Amyloid Precursor Protein Secretases; krystalografie rentgenová; oligosaccharide; inhibiční koncentrace 50; Enoxaparin; Crystallography, X-Ray; lidé; Alzheimer’s disease; enoxaparin; heparitinsulfát; molecular dynamics; Quantitative Structure-Activity Relationship; simulace molekulární dynamiky; virtual screening; Molecular Dynamics Simulation; algoritmy; oligosacharidy; Hydrogen Bonding; inhibitory enzymů; kvantitativní vztahy mezi strukturou a aktivitou; biologické přípravky; 3D QSAR pharmacophore modeling; Asp dyad; aspartátové endopeptidasy; Aspartic Acid Endopeptidases; Enzyme Inhibitors; Biological Products